Self‐reported cognitive function in a large international cohort of people with multiple sclerosis: associations with lifestyle and other factors. (14th September 2018) - Jelinek, P. L.; Simpson, S.; Brown, C. R.; Jelinek, G. A.; Marck, C. H.; De Livera, A. M.; O'Kearney, E.; Taylor, K. L.; Neate, S. L.; Weiland, T. J.
Abstract : Background and purpose: We aimed to estimate the prevalence of perceived cognitive impairment (PCI) and explore its associations with lifestyle and disease characteristics in a large international cohort of people with multiple sclerosis (MS). Methods: This study was a cross‐sectional analysis. Participants rated their cognitive function over the preceding 4 weeks using four questions in a subscale within the Multiple Sclerosis Quality of Life questionnaire (MSQOL‐54). These questions assessed perceived concentration, attention and memory by the patient and family/friends. Four definitions of PCI were derived, ranging from lowest to highest specificity. Associations with PCI were assessed by log‐binomial regression. Results: The prevalence of PCI in our sample ranged from 41.0% (95% confidence interval, 39.0–43.0) using the least‐specific definition to 11.6% (95% confidence interval, 10.3–12.9) using the most specific definition. A number of factors were associated with PCI, increasing in magnitude as the definition specificity increased, including positive associations for smoking and body mass index, whereas physical activity, dietary quality and use of vitamin D/omega‐3 supplements were inversely associated with PCI. Conclusions: Our study reports associations between healthy lifestyle behaviours and PCI in people with MS. Although reverse causality is a potential explanation for our findings, previous studies have shown comparable associations with healthy lifestyle and MS onset and progression. Subject to external validation, these results suggest benefits realized from a healthy lifestyle in people with MS.